Enhanced Image Encryption Using Pixel-Block Permutation and Multi-Chaotic Maps with DNA-Based Diffusion - Merdin Shamal Salih; Subhi R. M. Zeebaree (Journal of Soft Computing and Data Mining, 2025)
As differential and statistical attacks become more prevalent, enhancing image encryption is a significant concern. The proposed method in this study implements dual security enhancement by integrating pixel-level techniques with block-level modifications while utilizing Hénon for the red channel and Logistic for both the green and blue channels to achieve encryption. The encryption algorithm begins by dividing the image into four main blocks before performing multiscale scrambling of increasing sub-blocks through permutation. This approach aims to enhance confusion and diffusion by mixing the data through multilevel chaotic scrambling. The encryption process incorporates pixel-level confusion, subsequently followed by block scrambling to maximize the scrambling effect and complexity. During diffusion, the confused image undergoes two operations, including DNA encoding and XOR operations, to create robust data protection methods. Experimental results demonstrate that the proposed algorithm achieves strong encryption, evidenced by a high entropy value, minimal correlation, and key change sensitivity, verifying its resistance to differential and statistical analysis attacks. In conclusion, the method provides both good speed and security, making it a suitable choice for protecting and distributing images.